2016
DOI: 10.1136/neurintsurg-2016-012780
|View full text |Cite
|
Sign up to set email alerts
|

Safety, immediate and mid-term results of the newer generation of hydrogel coils in the treatment of ruptured aneurysms: a multicenter study

Abstract: Our data show that the use of the newer-generation hydrogel coils in the treatment of ruptured aneurysms is feasible, safe and effective with high immediate and mid-term occlusion rates and low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the Clinical and Anatomic Results in the Treatment of Ruptured Intracranial Aneurysms (CLARITY) study comparing BACE with CE in ruptured aneurysms, the authors found no difference in packing density; however, the use of BACE resulted in greater aneurysm occlusion rates (p=0.017) 23. In a study of newer generation hydrogel coils by Dabus et al , there was a trend towards higher rates of complete occlusion in the BACE group but no difference was noted in packing density between the groups 21. Interestingly, in our study, the BACE group demonstrated statistically significant greater rates of immediate occlusion (64% vs 47%; p=0.02) and an important statistical trend towards more complete occlusion on long term angiographic follow-up (64% vs 50%; p=0.09) compared with CE, despite similar packing density and significantly larger mean neck size in the BACE group.…”
Section: Discussionmentioning
confidence: 99%
“…In the Clinical and Anatomic Results in the Treatment of Ruptured Intracranial Aneurysms (CLARITY) study comparing BACE with CE in ruptured aneurysms, the authors found no difference in packing density; however, the use of BACE resulted in greater aneurysm occlusion rates (p=0.017) 23. In a study of newer generation hydrogel coils by Dabus et al , there was a trend towards higher rates of complete occlusion in the BACE group but no difference was noted in packing density between the groups 21. Interestingly, in our study, the BACE group demonstrated statistically significant greater rates of immediate occlusion (64% vs 47%; p=0.02) and an important statistical trend towards more complete occlusion on long term angiographic follow-up (64% vs 50%; p=0.09) compared with CE, despite similar packing density and significantly larger mean neck size in the BACE group.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand when it comes to postoperative assessments, several previous studies [ 33 , 34 ] have shown that the packing density of aneurysms treated with hydrogel coils was significantly higher, between 36% and 68%, than that of aneurysms treated with bare platinum coils [ 35 ]. In addition, hydrogel coils are more evenly distributed in the aneurysm sac, particularly in the neck of the aneurysm, which may be more helpful in achieving better occlusion rates [ 36 ]. However, these place greater demands on the operator’s surgical skills, and the effect of operator manipulation on coil outcomes is unavoidable and significantly confounding in the literature we included.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional and three-dimensional platinum coils can be applied for aneurysm sac embolism (a) and a typical threedimensional platinum coil (b) configuration from a primary (1°) to secondary (2°) to tertiary (3°) structure (c). IAs, AVMs and AVFs; peripheral vasculature embolization 79% [13] Orbit IAs, AVMs and AVF, peripheral vasculature 56% [18] Bioacti ve coils IAs, AVMs and AVF 77.8% [19] Matrix coil [20] Nexus [15] Submitted to 13 Ultipaq and Helipaq twodimensional filling coils AVF, arteriovenous fistula; AVM, arteriovenous malformation; GDC, Guglielmi Detachable Coil; PGA, polyglycolic acid; PLGA, polylactic-co-glycolic acid.…”
Section: Submitted Tomentioning
confidence: 99%